QORABAYIR OTLARNING O‘SISH VA RIVOJLANISH XUSUSIYATLARI - Xalilov Jahongir Zoxidovich; Alisher Ergashev Anvarjonovich (Educational Research in Universal Sciences, 2024)
It is important to take into account the laws of their growth and development when feeding cows. The rate of growth and development is different in different breeds, the live weight of foals at birth depends on the age and live weight of their mothers, while the live weight of steers is low. , from which a child with a small live weight is born and vice versa